Clinical Management of Maxillary and Mandibular Medication-Related Osteonecrosis of the Jaw Associated with Zoledronic Acid in a Patient with Multiple Myeloma: A Case Report - Cardoso, Nathália; Zanini, Isadora; Monção , Leandro Henrique; Ferreira, Bruna; Mota, Geovana Larissa; Manso, Maria Júlia; Pelegrine, Glenda; Azenha, Marcelo Rodrigues; Mariano Júnior, Wilson José; Watanabe, Sátiro; Bueno, Renan de Barros e Lima (Brazilian Journal of Case Reports, 2026)
Medication-related osteonecrosis of the jaws (MRONJ) is a complication associated with antiresorptive agents, including zoledronic acid. This condition occurs most frequently in patients undergoing treatment for malignant neoplasms, such as multiple myeloma. Diagnosis is primarily clinical and should be based on a thorough patient history, particularly regarding the use of antiresorptive medications, in conjunction with clinical examination and appropriate imaging studies. This report presents a clinical case of MRONJ in the maxillary region of a 78-year-old patient who received zoledronic acid for three years as part of multiple myeloma management. Sequestrectomy was selected as the surgical intervention, followed by the application of a Platelet-Rich Fibrin (PRF) membrane to the surgical site to serve as a protective barrier, control infection, and promote tissue repair. The patient demonstrated a favorable clinical outcome following these procedures. A carefully planned, appropriately indicated, and well-executed clinical approach offers a safe and effective alternative for the management of MRONJ. Prevention, early diagnosis, and individualized, multidisciplinary management are essential for achieving therapeutic success in these cases.